PELATIHAN AKUNTANSI PEPAJAKAN UNTUK MEMASUKI DUNIA KERJA DI SMAN 1 KOPO - Sugiyono Sugiyono; Abu Naim; Rosidawaty Rosidawaty; Rina Ambarwati; Ingkak Chintya Wangsih; Andika Mugi Gumilang; Dadang Dadang; Sena Atmaja; Helmas Septiyo Hadi; Dindin Aminudin; Ahmad Pauji (Jurnal Abdi Insani, 2025)
High school graduates need to have practical skills, especially in tax accounting, due to changes in the world of work. Many students are still confused about proper financial record-keeping and tax administration. Because of this situation, they are not prepared to meet the skill requirements needed by the industry. Therefore, SMAN 1 Kopo needs tax accounting training to provide students with relevant and practical skills. The community service activity "Tax Accounting Training for Entering the World of Work at SMAN 1 Kopo" aims to enhance students' knowledge and skills in tax accounting in accordance with the needs of the workforce. This activity began with an interactive seminar on the basics of taxation. Then, participants received hands-on training with simulations of simple accounting record-keeping, filling out tax returns, and using the e-filing application. To enhance their understanding, participants also engaged in group discussions and case studies. Pre-tests and post-tests were used to assess the students. The activity results showed that the students understood tax accounting better. A 45% increase in concept mastery occurred, from 25% on the pre-test to 70% on the post-test. This increase indicates that the practice-based learning and case study approach used during the training were highly effective. Students also became more confident in completing transaction journals and SPT simulations. This program successfully met its main objective, which was to prepare students from SMAN 1 Kopo to work with additional skills in tax accounting. This indicates that the socialisation and practical training methods successfully equipped students with tax accounting skills while also raising awareness of the importance of tax compliance.